Effectiveness of Psychological-Pedagogical Study of Adaptation of Elementary School Students to School - Nasimov Sadriddin Xurazboyevich (Researchparks Publishing, 2023)
This article analyzes the effectiveness and results of a psychological-pedagogical study of school adaptation of elementary school students.